The Effects of Hydrophobicity and Textural Properties on Hexamethyldisiloxane Adsorption in Reduced Graphene Oxide Aerogels - Xifeng Hou; Yanhui Zheng; Xiaolong Ma; Yuheng Liu; Zichuan Ma (Molecules, 2021)
To expand the applications of graphene-based materials to biogas purification, a series of reduced graphene oxide aerogels (rGOAs) were prepared from industrial grade graphene oxide using a simple hydrothermal method. The influences of the hydrothermal preparation temperature on the textural properties, hydrophobicity and physisorption behavior of the rGOAs were investigated using a range of physical and spectroscopic techniques. The results showed that the rGOAs had a macro-porous three-dimensional network structure. Raising the hydrothermal treatment temperature reduced the number of oxygen-containing groups, whereas the specific surface area (SBET), micropore volume (Vmicro) and water contact angle values of the rGOAs all increased. The dynamic adsorption properties of the rGOAs towards hexamethyldisiloxane (L2) increased with increasing hydrothermal treatment temperature and the breakthrough adsorption capacity showed a significant linear association with SBET, Vmicro and contact angle. There was a significant negative association between the breakthrough time and inlet concentration of L2, and the relationship could be reliably predicted with a simple empirical formula. L2 adsorption also increased with decreasing bed temperature. Saturated rGOAs were readily regenerated by a brief heat-treatment at 100 °C. This study has demonstrated the potential of novel rGOA for applications using adsorbents to remove siloxanes from biogas.